The Impact of Information and Communication Technology on Adolescents in Social Life - Rafly Muhammad Andika; Haliza Lufipah; Ahmad Rianda Lubis (Trigin Publisher, 2020)
Communication with the development of technology that is very fast in today's era. The development of science and technology makes it very easy for people to carry out their activities in daily life. Even today, almost everyone can't get away from communication technology, as is the case with young people. Adolescence is a period of transition from childhood to adulthood who have begun to be affected by the environment and already have the will to be what they want. With advances in communication technology that spurs teenagers to carry out more intensive identity-seeking activities by looking at the figures in the media. Developments in technology are directly proportional to the development of human needs for survival. One form of technology that has experienced rapid development in the last few decades is information technology. This will not be separated from a human need for communication because in essence that human behavior is to communicate. Technology has existed for a long time with the passage of time continues to take place in human life. Thus it is also that the development of technology is directly proportional to the development and level of human needs for survival. The more modern in human life, the more modern technology in the current era. This will not be separated from a human need for communication because in essence that human behavior is to communicate. Technology has existed for a long time with the passage of time continues to take place in human life. Thus it is also that the development of technology is directly proportional to the development and level of human needs for survival. The more modern in human life, the more modern technology in the current era. This will not be separated from a human need for communication because in essence that human behavior is to communicate. Technology has existed for a long time with the passage of time continues to take place in human life. Thus it is also that the development of technology is directly proportional to the development and level of human needs for survival. The more modern in human life, the more modern technology in the current era.